(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this study is to investigate how children with special needs feel about participating in regular classroom activities. To learn what’s going on and where we can start looking for answers, we need to look back at where we’ve been. The methodology of this study was qualitative, and the technique was descriptive. Data is collected using a variety of methods, including observation, interviews, and documentation, and then categorized and evaluated using a process that begins with the elimination of extraneous information and ends with the formulation of a conclusion. These results provide more evidence that unfavourable social views held by other students toward students with special needs have internal and external roots. These results also imply that kids with special needs suffer social limiting forces from the outside, especially those that stem from a general societal attitude of hostility. Some people just refuse to interact with families that have special needs. Having trouble relating to others and withdrawing from the world are common reactions to negative events and behaviours among children with special needs. As a rule, this is because of their history of poor decisions and acts. This makes it crucial that we figure out what’s triggering the response. Given the feasibility of these goals, a positive outlook is essential for children of all ages, including those with special needs and those growing normally.